Jawabanmu

2014-05-19T10:36:16+07:00
F(x)=(2k-1)x^2-(5k-1)x-(3k+1)=0

D>0
b²-4ac>0
(-5k+1)²-4(2k-1)(3k+1)>0
25k²-10k+1-24k²+4k+4>0
k²-6k+5>0
(k-6)(k-1)>0
k=6 atau k=1

2014-05-19T10:41:32+07:00
(2k-1) x²-(5k-1) x+(3k+1) = 0
Syarat D > 0 atau b² - 4ac > 0
{-(5k-1)}²-4(2k-1)(3k+1) > 0
25k² - 10k + 1 -4(6k²-k-1) > 0
25k² - 10k + 1 - 24k² + 4k + 4 > 0
k² -6k + 5 > 0
(k - 1)(k  - 5) > 0 terus pakai garis bilangan
+++++    - - - - -  ++++++
--------o----------o----------
           1            5
Jadi batas-batas nilai k adalah k < 1 atau k > 5